Quantum computation: From the sequential approach to simulated annealing - Castagnoli, G; Ekert, A; Macchiavello, C (1998)
This is a brief outline of some essential features of quantum computation. We describe sequential quantum data processing and speculate on new modes of quantum computation such as quantum annealing.